Smart Multi-Vehicle Parking System Using IoT - Chong, Wai Wai; Zainal, Mohd Shamian (Progress in Engineering Application and Technology, 2021)
In this era of modernization, vehicles on the road nowadays outpacing the supply of available parking space. The development of the smart parking system is essential in many places to overcome issues around the world. Nowadays, the parking areas are available more for light vehicles, instead of medium and heavy vehicles. Hence, in this project, the system allowed different types of vehicles such as light, medium and large size vehicle to fully utilized the available parking spaces. The main objective of this project is to provide precise occupancy information for the drivers which can help to reduce the time spent looking for a parking slot. Subsequently, the main feature of the smart multi-vehicle parking system is to detect the vacancy slot in the parking area by using ESP8266-01 and Arduino Mega 2560. Both of the mainboards will communicate with each other using TX and RX pin, at which the data is sent and give parking assignation to the user. The Blynk application allows the customer to choose their suitable vehicle types for parking space. The core sensor used in detection for the parking space and weather is based on the LDR sensor. Smart street lights will be an add-on feature in this system as it ensures the parking system can work even in a dark surrounding. Thus, it will turn on when the surrounding of the parking space starts to become gloomy. Besides that, the LCD provides real-time information for the customer too, thereby users are capable to know the availability of the parking space even at distant. The reservation feature is one of the limitations of this project, as the parking spaces are only for first come first serve. In conclusion, this multi-vehicle smart parking system with the user interface is user-friendly and convenient to use as it allows different types of vehicles to park.